(untitled) (Journal of Environment Sciences, 2025)
Heavy metals (HMs) in dust act as potential indicators of air pollution and pose significant risks to both human health and the environment. This study investigates the concentrations and pollution characteristics of six heavy metals (Cd, Cr, Cu, Ni, Pb, and Zn) in rooftop dust collected from three types of concrete buildings of varying heights: low-rise buildings (LRB), medium-rise buildings (MRB), and high-rise buildings (HRB) in the Kathmandu metropolitan area. A total of 36 dust samples were collected from the buildings during the dry season (March–April 2024) and analyzed for HMs content using flame atomic absorption spectrophotometry (FAAS). Pollution assessment was conducted using four indices: contamination factor (Cf), degree of contamination (Cdeg), pollution load index (PLI), and geo-accumulation index (Igeo). Results indicated that the mean HM concentrations were highest in dust from low-rise buildings, with all measured values exceeding background levels. The overall abundance of metals (mg/kg) in rooftop dust followed the order: Zn (372.0) > Cu (85.9) > Cr (69.3) > Ni (65.8) > Pb (56.2) > Cd (0.65). Pollution assessment using the contamination factor (Cf) and degree of contamination (Cdeg) revealed values ranging from 0.42 to 5.06 and 7.83 to 15.72, respectively, indicating low to considerable and considerable levels of contamination across all building types, with zinc (Zn) identified as the predominant pollutant. Pollution load index (PLI) values greater than 1.0 in this study confirmed that rooftop dust was polluted in all cases. Meanwhile, geo-accumulation index (Igeo) values ranging from 0.11 to 1.03 indicated a contamination level from unpolluted to moderately polluted. These findings suggest that vehicular emissions, industrial activities, construction and demolition, and other anthropogenic sources are the primary contributors to rooftop dust contamination in the metropolitan area.